From Dalit Struggles to Irish Defiance: Linguistic and Theological Hegemony as subversive tools of Marginalisation in the Dalit Experience of Himachal Pradesh and Irish Literary Resistance - Dr Sanjeev Kumar (Journal of Informatics Education and Research, 2025)
This paper investigates the manifestation of linguistic and theological hegemony by providing the parallel analysis between internal cultural domination in Himachal Pradesh through Sanskritised divine tradition and external cultural colonial domination in Ireland through British Anglicisation. Through incorporation of postcolonial and subaltern framework, the study explores how religious orthodoxy and linguistic imposition have corroborated hierarchical power, subdued subaltern voices, and shaped cultural memory. Cultural hegemony does not operate through political, economic and military ascendancy but through controlling belief, ritual, language and divine system which becomes the dominant form and processes of representation. In Himachal Pradesh and Ireland the hegemonic ideologies leverage these form and processes to exclude, marginalise and subdued subaltern voices. The primary objective of this study is to focus on Dalit experience in Himachal Pradesh where Sanskritised language and divine tradition are substantiated caste based exclusion. Likewise, in Ireland, colonial English is subjugated indigenous Gaelic traditions and marginalised native cultural identities. Hence, the paper examines how linguistic and cultural hegemony become a significant part of marginalisation showcasing a parallel study of two countries. Through a detailed and comprehensive comparative lens, the research analyses how cultural hegemony, whether internal (caste) colonisation in Shimla (Himachal Pradesh) is sustained by Sanskritised divine tradition and ritualistic power or external (colonial) colonisation in Ireland is operated by subjugating Gaelic tradition, silences subaltern voices, and how literature and oral traditions become significant medium of resistance to such domination.